Experiments with neutron beams for the astrophysical s process. Issue 1 (January 2016) - Lederer, C; Altstadt, S; Andrzejewski, J; Audouin, L; Barbagallo, M; Bécares, V; Bečvář, F; Belloni, F; Berthoumieux, E; Billowes, J; Boccone, V; Bosnar, D; et al.
Abstract: Neutron capture cross sections are the key nuclear physics input to study the slow neutron capture process, which is responsible for forming about half of the elemental abundances above Fe. Stellar neutron capture cross section can be measured by the time-of-flight technique, or by activation. Both techniques will be discussed and recent experiments in the Fe/Ni mass region will be presented.